PENGARUH DISIPLIN KERJA DAN KOMPETENSI TERHADAP KINERJA KARYAWAN PADA PT ANEKA TAMBANG TBK UNIT GEOMIN JAKARTA SELATAN - Aufa Salsabila Yusiani; Hira Maulida (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
This research aims to determine the effect of work discipline and competence on employee performance at PT Aneka Tambang Tbk Geomin Unit South Jakarta. The method used is a quantitative research method. The data collection technique used is saturated sampling. The research sample is 90 respondents. The data analysis method used in the study includes instrument testing consisting of validity testing, reliability testing, classical assumption testing consisting of normality testing, multicollinearity testing, heteroscedasticity testing, multiple linear regression testing, correlation coefficient testing, determination coefficient testing, hypothesis testing consisting of partial t-test and simultaneous f-test. From the results of this research it can be concluded that Work Discipline has a positive and significant effect on Employee Performance with a calculated t value> t table (4.463> 1.662) and a significance value of 0.000 <0.05. Thus, H01 is rejected and H1 is accepted. Competence has a positive and significant influence with a calculated t value > t table (4.881 > 1.662) and a significance value of 0.000 < 0.05. Thus, H02 is rejected and H2 is accepted. Work Discipline and Competence have a positive and significant influence on Employee Performance with a calculated F value = 17.523 > 3.101 or (calculated F > F table) and a significance value (0.000 < 0.05). Thus, H0 is rejected, and H3 is accepted. Work Discipline and Competence on Employee Performance have a regression effect of Y = 11.575 + 0.418 X1 + 0.277 X2 + a. The result of the R-square value (determination coefficient) is 0.287, so it can be concluded that the variables of work discipline (X1) and competence (X2) together have a contribution to the influence of the employee performance variable (Y) of 28.7%, while the remaining 71.3% is influenced by other factors or variables that are not examined.